BRS 430 B2RF and BRS 432 B2RF: Insect-resistant and glyphosate-tolerant high-yielding cotton cultivars - Suassuna,Nelson Dias (2018)
Abstract Transgenic cotton cultivars BRS 430 B2RF and BRS 432 B2RF, medium and late season respectively, were developed by EMBRAPA in partnership with Bahia Foundation, aiming to create a high-yielding germplasm. The Bt toxins Cry1Ac and Cry2Ab target lepidopteran pests and the CP4-EPSPS gene confers tolerance to the herbicide glyphosate.